Recent developments of MCViNE and its applications at SNS. (12th August 2019) - Lin, Jiao Y Y; Islam, Fahima; Sala, Gabriele; Lumsden, Ian; Smith, Hillary; Doucet, Mathieu; Stone, Matthew B; Abernathy, Douglas L; Ehlers, Georg; Ankner, John F; Granroth, Garrett E
Abstract: MCViNE is an open source, object-oriented Monte Carlo neutron ray-tracing simulation software package. Its design allows for flexible, hierarchical representations of sophisticated instrument components such as detector systems, and samples with a variety of shapes and scattering kernels. Recently this flexible design has enabled several applications of MCViNE simulations at the Spallation Neutron Source (SNS) at Oak Ridge National Lab, including assisting design of neutron instruments at the second target station and design of novel sample environments, as well as studying effects of instrument resolution and multiple scattering. Here we provide an overview of the recent developments and new features of MCViNE since its initial introduction (Jiao et al 2016 Nucl. Instrum. Methods Phys. Res., Sect. A810, 86–99), and some example applications.